WHAT NURSES MUST KNOW AND DO IN BLOOD TRANSFUSION - S. Assemi (Iran University of Medical Sciences, 2004)
Incredible advances in knowledge and technology that have been made in blood groups' identification, collection, fractionation, storage and related screening tests, have evolved transfusion medicine as a novel specialty of its' own. Feasibility of new surgical procedures is the result of these advancements. Infusing blood is a living transplantation procedure which carries its significant risks. So, its' usage must be limited to defendable and critical situations. Although, it is the physician's responsibility to order the transfusion therapy but nurses are those who perform it. Therefore, both groups should be knowledgeable enough to commit it and detect the adverse effects in order to intervene whenever necessary.